2022
DOI: 10.1186/s12889-022-13526-w
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of migration in an HIV hyper-endemic rural South African community: evidence from a population-based cohort (2005–2017)

Abstract: Globally, South Africa hosts the highest number of people living with HIV (PLHIV) and the unique legacy of internal labour migration continues to be a major driver of the regional epidemic, interrupting treatment-as-prevention efforts. The study examined levels, trends, and predictors of migration in rural KwaZulu-Natal Province, South Africa, using population-based surveillance data from 2005 through 2017. We followed 69 604 adult participants aged 15–49 years and recorded their migration events (i.e., out-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…7 Circular migration or the location of mines in impoverished remote communities also allows mining companies to pass the burden of healthcare back onto these poor rural areas. 8 The informal peri-mining communities that have sprawled around the mines provide easy access to alcohol, drugs and the sex industry, contributing to the spread of sexually transmitted diseases, including HIV. [10][11][12] The social issues around migrancy and masculinity and living conditions of mineworkers have contributed to a rapid transmission of HIV/AIDS and sexually transmitted infections.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…7 Circular migration or the location of mines in impoverished remote communities also allows mining companies to pass the burden of healthcare back onto these poor rural areas. 8 The informal peri-mining communities that have sprawled around the mines provide easy access to alcohol, drugs and the sex industry, contributing to the spread of sexually transmitted diseases, including HIV. [10][11][12] The social issues around migrancy and masculinity and living conditions of mineworkers have contributed to a rapid transmission of HIV/AIDS and sexually transmitted infections.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The associations between migration and HIV acquisition, care engagement, and HIV-related outcomes are complex and incompletely understood [ 5 , 21 ]. Some research has shown that people already living with HIV are more likely to migrate [ 22 , 23 ]. Other evidence shows that some migrants may be healthier when they leave their homes of origin, often called the “healthy migrant” hypothesis [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…South Africa’s decentralized health system is ill-suited for facilitating people changing clinics because it is difficult to easily transfer patient data across facilities [ 27 ]. Migrants also face other intersecting psychosocial and structural challenges which affect HIV and healthcare engagement, such as the disruption of relocation [ 22 ], lifestyle changes [ 5 ], unstable or lack of employment [ 21 ], isolation and difficult living conditions [ 25 ], lack of residency or citizenship documentation [ 28 ], and fear and language issues [ 29 ]. While some migrants nonetheless seek care in South Africa’s public healthcare system [ 30 ], research suggests that international migrants may also access healthcare at sites that are community-based or religiously-affiliated, especially where there are no fees or requirements for identity documentation or residence status [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations